Plastic as a Vector of Dispersion for Marine Species With Invasive Potential. A Review - García-Gómez, José Carlos; Garrigós, Marta; Garrigós, Javier (Frontiers in Ecology and Evolution, 2021)
Plastic debris constitute up to 87% of marine litter and are currently established as one of the most studied vectors of marine alien species with invasive potential. This review addresses an integrated analysis of the different factors required to understand the impact of plastics as a vector for the dispersal of species. The main vectors of ecosystem affection of plastics and their source of entry into the ocean are identified. The different transports described by plastic and how they affect the different trophic levels are studied, reviewing the hot spots of plastic accumulation in the ocean. The characterization of plastics as a dispersal vector for marine species provided information about inherent properties of plastics that have led to their impact on the ocean: persistence, buoyancy and variety in terms of chemical composition facilitate their colonization by macro and microscopic species, as well as its dispersion through the different oceans and ecosystems. The study of the differential colonization plastic types provided fundamental information to understand the invasion process mediated by plastic, as well as evidenced gaps in knowledge about this process. A wide range of species attached to plastic materials has been documented and the most recurrent phyla found in plastic have been identified: from potentially invasive macrofauna to toxic microorganisms, capable of causing great damage in places far away from their origin.